Sovereign debt structure for crisis prevention - Borensztein, Eduardo...[et al] (IMF WashingtonUS, 2004)
Considers recently developed analytical approaches to improving the structure of sovereign debt using existing debt instruments. Reviews a number of proposals - including the introduction of explicit seniority and GDP-linked instruments - in the sovereign context. Discusses their pros and cons and the related practical challenges.